Prasugrel Increases the Need for Platelet Transfusions and Surgical Reexploration Rates Compared with Clopidogrel in Coronary Artery Bypass Surgery - Drews, Susanne; Bolliger, Daniel; Kaiser, Christoph; Grapow, Martin; Reuthebuch, Oliver; Eckstein, Friedrich; Matt, Peter (The Thoracic and Cardiovascular Surgeon, 2015)
Background We hypothesized that patients treated with prasugrel compared with those treated with clopidogrel before coronary artery bypass graft (CABG) surgery are at increased risk of hemorrhagic complications needing transfusions and are more likely to need surgical reexploration.Patients and Methods Preoperative and postoperative clinical data were collected prospectively on 143 consecutive patients treated preoperatively with prasugrel (n = 59) or clopidogrel (n = 84) before undergoing isolated CABG at our institution from January 2011 to October 2012.Results Patients receiving prasugrel showed a slightly higher additive EuroSCORE I compared with those treated with clopidogrel (7 vs. 5, p = 0.001), and more often underwent urgent/emergent CABG (47 vs. 27%, p = 0.01). Patients treated with prasugrel were more likely than those treated with clopidogrel to need perioperative platelet transfusions (25 vs. 12%, p = 0.04). The numbers of transfusions of red blood cells, fresh-frozen plasma, or fibrinogen were high in both groups but showed no statistical differences. Patients treated with prasugrel, however, more often needed surgical reexploration for bleeding complications (8 vs. 1%, p = 0.03). Logistic regression revealed that preoperative therapy with prasugrel (RR 2.9, p = 0.01) and urgent/emergent surgery (RR 2.2, p = 0.04) were predictors for the composite endpoint “need for perioperative platelet transfusion and/or surgical reexploration.”Conclusion Pretreatment with prasugrel, compared with clopidogrel, in patients undergoing isolated CABG is associated with an increased need for platelet transfusions and a higher risk of surgical reexploration for bleeding complications.
Keywords: blood transfusion; blood; coagulation/anticoagulation; coronary artery bypass grafts surgery